Removal of heavy metals in industrial wastewater using adsorption technology: Efficiency and influencing factors - Fernando García Ávila; Janneth Cabrera-Sumba; Sandra Valdez-Pilataxi; Jessica Villalta-Chungata; Lorgio Valdiviezo-Gonzales; Cecilia Alegria-Arnedo (Cleaner Engineering and Technology)
Most industries are responsible for environmental pollution because their wastewater contains heavy metals that are hazardous. These metals tend to persist indefinitely in the environment, compromising not only human health but also the well-being of ecosystems. The objective of this study was to analyze the adsorption technology for removing heavy metals in industrial wastewater, evaluating influencing factors, adsorbent materials, applied isotherms and their advantages, through a systematic review of the scientific literature of the last 10 years. To conduct this research, the Scopus digital database was consulted. The search was conducted using a systematic review methodology and the PICO framework to identify, analyze, and interpret data on adsorption technology, factors influencing adsorption, the efficiency of different materials used as adsorbents, and the advantages and disadvantages of adsorption isotherms. To filter the information, the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement were followed, which allowed the articles to be selected to answer the research questions posed in this study. Based on the results, it was found that the factors influencing the adsorption of heavy metals include pH (range of 3–9), contact time (range of 10–14,400 min), adsorbent dosage (0.011–20 g/L), temperature (25–30 °C), particle size, and agitation speed (100–800 ppm). Among the most efficient adsorbents are acacia cellulose lignin with 99.8% Cr, bentonite clay with 99% Cu, 96% Cd, and 99% Pb, modified sugarcane bagasse with 96.9% Cu, and activated carbon with 82.8% Cr at pH 3. The least efficient adsorbents are natural moss (54.5% Cr) and biochar from corn husks (20% Cr). The Freundlich isotherm model is the most used, and it can vary depending on the type of adsorbent, the correlation coefficient fit, and the type of heavy metal being treated. Finally, the advantages and limitations of some adsorbents are presented, primarily highlighting their low costs, reusability, and the sustainability they can offer in reducing environmental pollution.